Faktor Resiko Kejadian Preeklampsia Di Rumah Sakit Umum Daerah Moewardi Surakarta Tahun 2023 - Evita Cahya Wardani; Sulastri Sulastri (Lembaga Pengembangan Kinerja Dosen, 2024)
Using the variables of maternal age, gravida status, history of preeclampsia, chronic hypertension, and diabetes mellitus, this study attempts to identify the risk factors for the occurrence of preeclampsia in mothers giving birth at Dr. Moewardi Hospital, Surakarta. This study employs an analytical observational research design. The case control design is employed in this study. Retrospective research designs are well-known for this one. Secondary data are the sort of data used in this study. All patients diagnosed with preeclampsia at Dr. Moewardi Hospital in Surakarta between 2020 and 2023 comprised the study's population. The study's findings demonstrated the features of mothers giving delivery at Dr. who had a history of preeclampsia in their families (20.5%), chronic hypertension in their families (25.9%), or diabetes mellitus in their families (14.5%).